Can the anaesthetic induced liquid-to-gel phase transition temperature depression be behind the molecular mechanism of general anaesthesia? - Hantal, György; Bánovská, Sára; Varga, Lukács; Fábián, Balázs; Mihály, Judith; Jedlovszky, Pál (Journal of Molecular Liquids, 2024)
We report differential scanning calorimetry (DSC) measurements and extensive computer simulations to determine the gel (Lβ’) to liquid crystalline (Lα) phase transition temperature of the neat 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) membrane as well as DPPC membranes containing different amount of general anaesthetics of various kinds. In addition, measurements are reported on liposomes consisting of molecules that are chemically or, at least structurally similar to certain general anaesthetics, but lack the anaesthetic effect themselves. The aim of the study is to test one of the competing hypotheses that aims at explaining the molecular mechanism of general anaesthesia by relating it to the anaesthetic-induces depression of the temperature of the aforementioned phase transition. Our results, however, do not confirm this conjecture. Thus, while diethyl ether, a well-known general anaesthetic is found not to induce any depression of the phase transition temperature, carbon tetrachloride, a molecule having no anaesthetic effect induces a larger decrease of this temperature than any general anaesthetic considered here. Furthermore, the computer simulations performed reveal that, in fact, none of the two conditions lying behind this conjecture, i.e., that anaesthetics are ideally dissolved in the Lα but do not dissolve at all in the Lβ’ phase, are satisfied. Therefore, we rule out not only a causal relation, but even a simple correlation between the membrane phase transition depression caused by dissolved molecules and the phenomenon of general anaesthesia.
CRIS-Team Scopus Importer:2024-10-25
Keywords: DPPC bilayer; DSC measurements; General anaesthesia; Molecular dynamics simulation; Phase transition point depression